Media Shifting: A Study of Generation Z's Preferences on Television and Digital Platforms - Latief, Rusman; Suradi; Soefijanto, Totok Amin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
This study aims to understand Generation Z's media preferences and provide strategic recommendations for the media industry, particularly television and digital media, in maintaining relevance in the hybrid media era. The urgency of this research lies in its contribution to the development of mass communication studies, while also providing practical insights for media managers in designing programs that are adaptive, credible, and appropriate to the needs of the younger generation, especially Gen Z. This study used a Focus Group Discussion (FGD) method to examine Generation Z's arguments on media practices and expectations regarding television and digital platforms, represented by university students. The results showed that digital platforms, including social media, YouTube, and Netflix, were preferred due to their accessibility, flexibility, and suitability for a multitasking lifestyle. However, participants considered information on social media to be less credible, and they still considered television to have advantages due to its disciplined production standards. A nostalgic phenomenon among students also emerged, particularly educational television programs from the 2000s, which can be utilized in the future by combining traditional values with contemporary innovation. Referring to the Uses and Gratification theory, this study confirms that Generation Z is an active group of media users who consume content to fulfill social, cognitive, entertainment, and personal identity needs.